2018
DOI: 10.1101/332015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of monomeric full-length ARC sheds light on molecular flexibility, protein interactions, and functional modalities

Abstract: The activity-regulated cytoskeleton-associated protein (ARC) is critical for long-term synaptic plasticity and memory formation. Acting as a protein interaction hub, ARC regulates diverse signalling events in postsynaptic neurons. A protein interaction site is present in the ARC C-terminal domain (CTD), a bilobar structure homologous to the retroviral Gag capsid domain. However, knowledge of the 3-dimensional structure of full-length ARC is required to elucidate its molecular function. We purified recombinant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 65 publications
3
49
0
1
Order By: Relevance
“…Taken together, these data suggest that the C-terminal tail has minimum (if any) interaction with the N-lobe and C-lobe (together they form the capsid domain), and it does not affect the folding of the capsid domain. This observation agrees with a previous finding that the C-terminal tail lies outside the core of the Arc protein, which is consisted of the Arc N-terminus sitting above the capsid domain [19]. However, further experiments are required to examine the possible interaction between the C-terminal tail and the capsid domain.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, these data suggest that the C-terminal tail has minimum (if any) interaction with the N-lobe and C-lobe (together they form the capsid domain), and it does not affect the folding of the capsid domain. This observation agrees with a previous finding that the C-terminal tail lies outside the core of the Arc protein, which is consisted of the Arc N-terminus sitting above the capsid domain [19]. However, further experiments are required to examine the possible interaction between the C-terminal tail and the capsid domain.…”
Section: Plos Onesupporting
confidence: 91%
“…They found that Arc’s coiled-coil subdomain (Arc 26-130 ) lies above its bi-lobe subdomain (Arc 210-361 ), and its N- and C-terminal tails lie at opposite ends. They also found that ligand binding to Arc’s N-lobe did not cause major conformational changes to the rest of the protein [ 19 ]. Furthermore, Nielsen et al produced the capsid domain of rat Arc (Arc 206-364 ) that includes the N-lobe and the C-lobe, and solved its structure using the solution NMR method [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The details of the protein constructs are given in S1 Table. The expression and purification of human Arc NL and CL have been described [17].…”
Section: Methodsmentioning
confidence: 99%
“…The Arc-NT is predicted to have homology to the retroviral matrix domain and is required for the formation of large mArc oligomers. Without its N-terminal domain, mArc is monomeric in solution [17]. In mArc, it is likely that the presence of both mArc-NT and mArc-CT are required for high-order oligomerization and capsid formation [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation